(untitled) (Global Journal of Human-Social Science, 2014)
This paper intends to explore the Socio-Economic contribution of Institution of Madresa in Pakistani society while critically evaluating the authenticity of criticism against the institution which has surfaced after the 9/11 incident, accusing Madresa to be the breading ground of militancy, terror networks and sectarian violence. Additionally the paper explores the free-for-all service of Madresa in providing education, increasing literacy rate and employability for the poorest of the poor. It is discovered that Madresa provide a near equivalent of primary to tertiary levels of education by only spending almost half the amount spent by its conventional counterparts in the country. Along with this residential Madaris save the poorest of children from various illegal activities including child prostitution.